Eksistensi Metode Cramer Sebagai Solusi Penyelesaian SPL Dalam Kasus Rangkaian Listrik - Devita, Rischa (CV RIFAINSTITUT, 2022)
In this paper, the existence of the Cramer method is discussed as a solution to solving SPL in the case of electrical circuits. The Cramer method is a method used in the problem of solving systems of linear equations. The Cramer method was invented by a mathematician from Switzerland named Gabriel Cramer in 1704-1752. The steps that must be done in calculating the strength of the current flowing in a circuit are. (1) By applying Kirchoff's Law obtained several equations, (2) Write the equations obtained from step 1 into a system of equations, (3) Represent the system of equations into a form of matrix multiplication, (4) Calculate the values of the current strength using the formula of the Cramer method. The Cramer method provides a good solution to facilitate the calculation of the strong value of electric current flowing in an electrical circuit.Matrix,